FBXW4 Is Highly Expressed and Associated With Poor Survival in Acute Myeloid Leukemia - Han, Qi; Zhang, Qi; Song, Huihui; Bamme, Yevgeniya; Song, Chunhua; Ge, Zheng (Frontiers in Oncology, 2020)
The F-box and WD repeat domain-containing (FBXW) proteins play an important role in ubiquitin proteasome by inducing protein degradation. Ten FBXW proteins have been identified in humans. The functions of FBXW proteins, like FBXW7, have been well-established in many human cancers. However, little is known about their transcriptional expression profiles and relationship with prognosis in acute myeloid leukemia (AML). Here we investigated the roles of FBXW proteins in AML by analyzing their mRNA expression profiles and association with clinical features using data from EMBL-EBI, the Cancer Cell Line Encyclopedia, Gene Expression Profiling Interactive Analysis, and cBioPortal databases. Our results showed that the mRNA level of FBXW proteins were highly detected by microarray in 14 AML cell lines, although there were no obvious differences. The expression of FBXW4 was significantly higher in AML patients compared with that in normal controls (P < 0.01). Patients whose age was ≥60 years old had a higher FBXW4 expression when compared with those who were <60 years old (P < 0.05). Cytogenetic favorable-risk group patients had a much lower FBXW4 expression than the intermediate- and poor-risk group patients (P < 0.0001). Moreover, patients with high FBXW4 expression exhibited significantly shorter event-free survival (EFS) and overall survival (OS) than those with low FBXW4 expression (median EFS: 5.3 vs. 10.0 months, P = 0.025; median OS: 8.1 vs. 19.0 months, P= 0.015). A multivariate analysis indicated that high FBXW4 expression was an independent risk factor for poor EFS in AML patients who received intensive chemotherapy followed by allo-SCT. In summary, our data suggested that FBXW4 is aberrantly expressed in AML and high FBXW4 expression might be a poor prognostic biomarker; future functional and mechanistic studies will further illuminate the roles of FBXW4 in AML.